Long non-coding RNA CYTOR promotes the progression of melanoma via the miR-485-5p/GPI axis - Lu, Haitao; Zhao, Yunhua; Zhang, Yanli; Shi, Shaomin; Hu, Huanrong; Li, Xuefei; Niu, Yandong; Qi, Haihua; Ji, Shang; Duan, Xinsuo; Liu, Yaling (PeerJ, 2025)
Background Recent research has underscored the critical role of long non-coding RNAs (lncRNAs) in tumorigenesis and malignancy development. Nevertheless, the role of lncRNA cytoskeleton regulator RNA (CYTOR) in the progression of melanoma remains only partially elucidated. This research seeks to explore the impact of CYTOR on melanoma development and to elucidate the molecular mechanisms involved. Methods In vitro and in vivo models were used to assess CYTOR expression levels by QPCR and Western blotting. Melanoma cell proliferation, migration, and invasion were assessed by CCK-8 assay, scratch wound assay and transwell invasion experiments. The mechanism of CYTOR promoting melanoma progression was verified in a xenograft tumor mouse model. Results Our investigation identified a marked increase in CYTOR expression levels in both melanoma tissues and cells. Experiments conducted both in vitro and in vivo revealed that CYTOR markedly stimulated melanoma cell proliferation, migration, and invasion. Dual-luciferase reporter assays confirmed the direct binding of miR-485-5p to CYTOR, and glucose-6-phosphate isomerase (GPI) was identified as a direct target of miR-485-5p.
Keywords: Melanoma; CYTOR; miR-485-5p; GPI